2014
DOI: 10.1111/jcmm.12405
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide decreases IL‐1β‐induced activation of fibroblast‐like synoviocytes from patients with osteoarthritis

Abstract: Balneotherapy employing sulphurous thermal water is still applied to patients suffering from diseases of musculoskeletal system like osteoarthritis (OA) but evidence for its clinical effectiveness is scarce. Since the gasotransmitter hydrogen sulphide (H2S) seems to affect cells involved in degenerative joint diseases, it was the objective of this study to investigate the effects of exogenous H2S on fibroblast-like synoviocytes (FLS), which are key players in OA pathogenesis being capable of producing pro-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 44 publications
1
35
0
3
Order By: Relevance
“…Since persistent tissue damage, MODS and high mortality rate are highly associated with oxidative stress and cytokine storm induced by influenza and other severe viral infections hydrogen can significantly reduce oxidative stress and restrain excessive production of cytokines [9, [57][58][59][60]. We hypothesize that hydrogen can be potentially effective for MODS induced by influenza and other viral infectious diseases.…”
Section: Novel Vaca S1d Signal Sequence Found In Helicobacter Pylori mentioning
confidence: 99%
“…Since persistent tissue damage, MODS and high mortality rate are highly associated with oxidative stress and cytokine storm induced by influenza and other severe viral infections hydrogen can significantly reduce oxidative stress and restrain excessive production of cytokines [9, [57][58][59][60]. We hypothesize that hydrogen can be potentially effective for MODS induced by influenza and other viral infectious diseases.…”
Section: Novel Vaca S1d Signal Sequence Found In Helicobacter Pylori mentioning
confidence: 99%
“…Estudos realizados por Nozawa-Inoue et al (2003) demonstraram que ocorre aumento de células do tipo A na inflamação da membrana sinovial e que essas células são capazes de produzir substâncias pró-inflamatórias como o óxido nítrico (NO) produzido pela enzima óxido nítrico sintase induzível (iNOS). As células do tipo B, por sua vez, são caracterizadas pela presença de um retículo endoplasmático rugoso bem desenvolvido e grânulos secretórios, e são responsáveis por produzir e secretar componentes do fluido sinovial e da matriz extracelular, incluindo ácido hialurônico, colágeno e fibronectina, presentes no líquido sinovial, bem como mediadores envolvidos em processos inflamatórios como citocinas e enzimas metaloproteinases de matriz (Iwanaga et al, 2000;Sieghart et al, 2015). O líquido sinovial consiste em um dialisado de plasma sanguíneo com grandes quantidades de ácido hialurônico e glicosaminoglicanos com viscosidade suficiente para manter lubrificadas as superfícies articulares.…”
Section: Articulação Temporomandibularunclassified
“…Neste sentido, as células sinoviais semelhantes a fibroblastos (FLS) desempenham um papel fundamental na progressão da inflamação na ATM devido a sua capacidade de produzir um grande número de mediadores inflamatórios (Kardel et al, 2003;Satoh et al, 2009;Sieghart et al, 2015).…”
Section: Processo Inflamatório Na Sinoviteunclassified
“…In their study, Sieghart et al concluded that exogenous H2S (NaHS) reduced the IL-1β-induced activation of fibroblast-like synoviocytes obtained from arthrosis patients, probably via the MAP-kinase and PI3K/Akt pathways [29].…”
Section: Evidences Of the Sulfur Water Effectsmentioning
confidence: 99%